Effects of acute ingestion of different fats on oxidative stress and inflammation in overweight and obese adults - Peairs, Abigail D; Rankin, Janet W; Lee, Yong Woo (Nutrition journal, 2011)
Studies show that obese individuals have prolonged elevations in postprandial lipemia and an exacerbated inflammatory response to high fat meals, which can increase risk for cardiovascular diseases. As epidemiological studies indicate an association between type of fat and circulating inflammatory markers, the purpose of this study was to investigate the acute effect of different fat sources on inflammation and oxidative stress in overweight and obese individuals. Eleven overweight and obese subjects consumed three high fat milkshakes rich in monounsaturated fat (MFA), saturated fat (SFA), or long-chain omega 3 polyunsaturated fat (O3FA) in random order. Blood samples collected at baseline, 1, 2, 4, and 6 hours postprandial were analyzed for markers of inflammation (soluble intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), tumor necrosis factor- α (TNF-α), and C-reactive protein (CRP)), oxidative stress (8-epi-prostaglandin-F2α (8-epi) and nuclear factor-κB (NF-κB)), and metabolic factors (glucose, insulin, non-esterified free fatty acids, and triglycerides (TG)). O3FA enhanced NF-kB activation compared to SFA, but did not increase any inflammatory factors measured. Conversely, SFA led to higher ICAM-1 levels than MFA (p = 0.051), while MFA increased TG more than SFA (p < 0.05). CRP increased while TNF-α and 8-epi decreased with no difference between treatments. While most of the inflammatory factors measured had modest or no change following the meal, ICAM-1 and NF-κB responded differently by meal type. These results are provocative and suggest that type of fat in meals may differentially influence postprandial inflammation and endothelial activation.